1994
DOI: 10.1177/004051759406400702
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fluoroalkylation of Polyester Surfaces: Grafting with Perfluoroalkanoyl Peroxides

Abstract: Perfluoroalkanoyl peroxides such as (C3F7COO)2 have been found to react with polyester film only on the surface. The modified polyester surfaces were characterized by contact angle measurements using a two-liquid phase system and by ESCA spec troscopy. These provided surface free energy values and surface atom content values as a function of reaction time. Perfluoroalkyl groups substituted on the aromatic rings of the polyester surface influenced both the dispersive component γsd of surface free energy and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…216 Recently, these fluoroalkanoyl peroxides were used in the direct aromatic fluoroalkylations of the surface only of polyester film and to the surface modification of silk fabric. 217,218 Polymers bearing benzene rings such as polystyrene, poly(2,6-dimethyl-p-phenylene oxide), and poly-(diphenylacetylene) were chemically modified using fluoroalkanoyl peroxides. These fluoroalkylated polymers were shown to have higher gas permeabilities than the parent polymers.…”
Section: Aromatic Fluoroalkylation Of Polymeric Compounds With Fluoro...mentioning
confidence: 99%
See 1 more Smart Citation
“…216 Recently, these fluoroalkanoyl peroxides were used in the direct aromatic fluoroalkylations of the surface only of polyester film and to the surface modification of silk fabric. 217,218 Polymers bearing benzene rings such as polystyrene, poly(2,6-dimethyl-p-phenylene oxide), and poly-(diphenylacetylene) were chemically modified using fluoroalkanoyl peroxides. These fluoroalkylated polymers were shown to have higher gas permeabilities than the parent polymers.…”
Section: Aromatic Fluoroalkylation Of Polymeric Compounds With Fluoro...mentioning
confidence: 99%
“…Recently, these fluoroalkanoyl peroxides were used in the direct aromatic fluoroalkylations of the surface only of polyester film and to the surface modification of silk fabric. , …”
Section: Aromatic Fluoroalkylation Of Polymeric Compounds With Fluoro...mentioning
confidence: 99%
“…Previously, we studied the fluoroalkylation of the polyester surface and we showed that the fluoroalkyl groups introduced on the polyester surface influenced the surface free energy [19]. We also found that the F ls to 0 Is ratio as determined by XPS was linearly correlated to both and y/.…”
Section: Relationship Between the Surface Energies And Xps Characterimentioning
confidence: 70%